Adaptasi Guru di Era Pendidikan Berbasis Digital - Icam Sutisna; Rachmah Safitri (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
Education as a process continues to change from time to time. According to Eric Ashby (1972), education has undergone five processes of change to date. According to him, education at this time uses more information and communication technology in the learning process. Information and communication technology has changed the classical education model into a virtual one. The educational process is no longer limited by space and time. Anywhere, anytime, every learner can carry out learning activities, without having to wait for a schedule. That is the reality of education now, whether we like it or not, the changes have occurred in the world of education. This is education in the digital era that has been predicted by many people in the past.